Rection of abaca (Musa textilis Nee.) accessions and varieties to fusarium wilt caused by Fusarium oxysporum f.sp. cubense (E.F. Smith) Snyd. And Hans. - Borines, Lucia M.; Salamat, Elsie E.; Cardines, Rammel B. (Annals of Tropical Research, 2007)
Fusarium wilt caused by Fusarium oxysporum f.sp. cubense (FOC) is one of the problem diseases attacking abaca. The most effective way of minimizing the damage is through the use of resistant varieties. The levels of resistance of different abaca varieties/accessions, however, have not been determined yet so this study was conducted to: 1) evaluate the reaction of eight recommended abaca varieties to fusarium wilt, 2) evaluate the reaction of abaca varieties/accessions and abaca relatives from the National Abaca Research Center (NARC) germplasm collection and production area to fusarium wilt, and 3) confirm the reaction of the identified resistant varieties/accessions in a naturally infested field. Among the 8 recommended abaca varieties, Linino showed resistance to FOC having the lowest infection, foliage yellowing and internal vascular discoloration ratings in a pot experiment. This variety was also proven resistant in the field plot screening together with 6 other accessions, namely: Alman No. 2, Alman No. 4, Tinawagan Puti #. 2, Pakol, CES x Pacol and Pakil # 1. Of the six, Alman No. 4, Tinawagan Puti # 2, Linino and Pakil also showed resistance to FOC, when planted in a naturally infested field in Polahongon, Mahaplag, Leyte.